Postcolonial Memories and Emotional Dislocation in Zimbabwean Literature: A Study of Noviolet Bulawayo’s We Need New Names - Agyo, Azetu; Ogba, Martins; Isah, Materclaus (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This study examines the intersection of colonial and postcolonial memories, gender, and emotional dislocation in NoViolet Bulawayo’s We Need New Names (2013). It explores how the novel portrays the enduring legacies of colonialism in shaping identity, cultural hybridity, and psychological experiences. While previous research has addressed themes of migration and cultural alienation in Bulawayo’s work, there is limited analysis of the novel’s engagement with colonial and postcolonial memories, particularly through the lens of gender and emotional trauma. This study addresses this gap by investigating how colonialism’s lingering effects continue to shape individual and collective identities in postcolonial Zimbabwe. This research is grounded in postcolonial theory and trauma theory. Drawing on Edward Said, Homi Bhabha, and Frantz Fanon, the study examines hybrid identities and the internalization of colonial hierarchies. Additionally, trauma theory, as articulated by Cathy Caruth and Marianne Hirsch, provides insight into the emotional and psychological dislocation experienced by the characters, particularly in relation to migration and the intergenerational transmission of colonial trauma. A qualitative methodology is employed, using textual analysis and discourse analysis to examine the novel’s representation of colonial legacies. We Need New Names was selected due to its critical engagement with postcolonial identity and migration. Findings reveal that colonial structures persist in economic struggles, cultural hybridity, and emotional alienation. Darling’s migration to America highlights identity fragmentation, while language and cultural hybridity shape postcolonial selfhood. This research contributes to discussions on postcolonial identity, migration, and trauma. It underscores literature’s role in reflecting historical and socio-political realities and deepens our understanding of identity formation in postcolonial societies.